CHRONOLOGICAL DIMENSIONS OF THE DEVELOPMENT OF FASHION SHOWS - Dykhnych, Ludmila (Theory and practice of design, 2025)
The purpose of the article is to identify the main stages of the history and development of fashion shows, to describe them in chronological order. Methodology. The study uses chronological, historical, biographical, analytical methods, as well as the method of systematisation, figurative and stylistic analysis of models of designers’ collections and photographic materials.Results. Based on the results of the analysis of the experience of fashion shows in historical evolution, nine main stages of their development have been identified: Paris, France, Florence, Milan, Italy); 1960s: prêt-à-porter shows; 1970s: creation of the combined Paris Haute Couture and prêt-à-porter fashion week under the auspices of the French Fashion Federation; 1980s.: London Fashion Week was launched in London (UK); 1990s: the era of supermodels and a variety of locations; 2000s: a variety of locations, internet technologies and Instagram.Scientific novelty. For the first time in art history research on design, fashion shows are analysed in chronological order from the second half of the nineteenth century to the present. The sources of the research were photographs from the shows, scientific and analytical materials on the work of designers.Practical relevance. The results of the study are the basis for the compilation of monographs, textbooks, lecture courses on the history of design and the history of modelling.